Rediscovery of little-known-monotypic genus Karnataka P.K.Mukh. & Constance (Apiaceae) - Gosavi, Kumar Vinod Chhotupuri; Madhav, Nilesh Appaso; Khandige, Vikas Bhat; Chandore, Arun Nivrutti (Phytotaxa, 2023)
Karnataka (Apiaceae) is a monotypic genus rediscovered after it’s type collection around 175 years from Mudbidri area of Dakshina Kannada (South Canara) district, Karnataka. Detailed morphological description, identity notes and photoplates have been provided based on fresh material collected by authors.